THE EFFECT OF PICTURE WORD INDUCTIVE MODEL ON STUDENTS' WRITING ABILITY - Komalasari, Fanny; Yuvita, Yuvita; Wardhani, Sri (LPPM Universitas Pancasakti Tegal, 2019)
The objective of this research is to find out the effect of the Picture Word Inductive Model on students? writing skills in writing descriptive text.  The Picture Word Inductive Model is a great strategy for teaching writing, especially writing descriptive text. Quantitative analysis is applied to draw findings of this research by using pre-experimental research in which the pretest and posttest design is adopted. The sample of this research is 31 students of junior high school. The data of the research is collected through writing tests distributed before and after the treatment.  The improvement of the mean value of pretest and posttest is used to analyze the impacts on students?  writing ability. Further, the T-test is used to prove the hypothesis to reveal the effectiveness of the model in teaching writing descriptive text. The result shows that the Picture Word Inductive Model (PWIM) is effective to teach writing descriptive text and it gives a positive effect on students? writing skills.